PENGEMBANGAN KECERDASAN MUSIKAL MELALUI KEGIATAN TEBAK LAGU BERBASIS INSTRUMEN UNTUK ANAK USIA 5 – 6 TAHUN - Tiara sari; Hanum Maulidah; Siti Esma Sari; Sri Indriani Harianja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the development of musical intelligence through song guessing activities based on the piano instrument for children aged 5-6 years. Through a comprehensive literature study, this research analyzes various aspects of children's development that can be stimulated through interactive musical activities. The research results show that instrument-based song guessing activities have significant potential in improving children's auditory abilities, musical memory, social skills, creativity, music-language connections and emotional awareness. This study also underscores the importance of post-activity discussions in strengthening children's musical understanding. Based on literature findings, a design for song guessing activities using pianists in small groups is proposed as a practical method for developing musical intelligence of children aged 5-6 years